EFFECT OF COLORS ON SOCIETY: समाज पर रंगों का प्रभाव - Yadav, Neetu (International Journal of Research -GRANTHAALAYAH, 2014)
Every object in the world has a texture that has a form and color, which gives importance to their identity, any object can be identified by its form, shape and color, if the object has only shape Looks dull. Of all the elements in the picture, the most emotional element is the character. A character is like a wave, which gives life to an object. Color is a quality of light rays that we experience through our eyes. We can show the true nature of an object only through colors. So that it has an impact on the person seeing. Color is not only an object but also a means of understanding emotions. संसार की प्रत्येक वस्तु की एक बनावट होती है जिसका एक रूप और रंग होता है, जो उनकी पहचान को महत्व प्रदान करता है, किसी भी वस्तु को उसके रूप, आकार व रंग से पहचाना जा सकता है, यदि वस्तु में केवल आकार हो तो वह नीरस दिखाई देती है। चित्र के समस्त तत्वों में सबसे अधिक संवेगात्मक तत्व वर्ण होता है। वर्ण एक प्रकार की लहर के समान होता है, जो वस्तु को जीवन प्रदान करता है। रंग प्रकाष की किरणों का एक गुण है जिसका अनुभव हम अपने नेत्रों के माध्यम से करते हैं। किसी वस्तु के वास्तविक स्वरूप को हम रंगों के द्वारा ही प्रदर्षित कर सकते हैं। जिससे कि देखने वाले व्यक्ति पर उसका प्रभाव पड़े ।रंग वस्तु को ही नहीं बल्कि भावनाओं को समझने का भी एक साधन है।